Correlation between circulating fibrocytes, and activity and progression of interstitial lung diseases - FUJIWARA, ATSUSHI; KOBAYASHI, HIROYASU; MASUYA, MASAHIRO; MARUYAMA, MITSUKO; NAKAMURA, SHIHO; IBATA, HIDENORI; FUJIMOTO, HAJIME; OHNISHI, MASAHIRO; URAWA, MASAHITO; NAITO, MASAHIRO; TAKAGI, TAKEHIRO; KOBAYASHI, TETSU; et al. (Respirology (Carlton, Vic.), 2012)
ABSTRACT Background and objective:  Interstitial lung diseases (ILD) are characterized by progressive interstitial pulmonary fibrosis and a decline in lung function. Fibrocytes are bone marrow‐derived mesenchymal progenitor cells that may play a role in the pathogenesis of pulmonary fibrosis. Circulating fibrocyte numbers have been correlated with the prognosis of patients with idiopathic pulmonary fibrosis. The aim of the present study was to evaluate the relationship between circulating fibrocytes, and parameters of disease activity and progression in several groups of patients with ILD. Methods:  The study population comprised 41 patients with ILD and seven healthy control subjects. Circulating CD45+ collagen‐I+ fibrocytes were evaluated by flow cytometry. Results:  The number of circulating fibrocytes was significantly increased in all patients with ILD and particularly in patients with idiopathic interstitial pneumonitis and interstitial pneumonitis associated with collagen vascular disease as compared with healthy control subjects. The numbers of circulating fibrocytes were significantly correlated with pulmonary function test parameters and with serum levels of sialylated carbohydrate antigen, a marker of disease activity. Temporal changes in circulating fibrocyte numbers were evaluated in two patients, and the results suggested that these changes correlated with the activity of ILD. Conclusions:  The results from this study provide further evidence for the role of circulating fibrocytes in fibrotic lung diseases. Circulating fibrocytes may play a role in pulmonary fibrosis and clinical outcomes. This study demonstrated that high numbers of circulating fibrocytes correlated with pulmonary function test parameters and disease activity in patients with different interstitial lung diseases. It provides further support for the potential role of fibrocytes in pulmonary fibrosis.